Reference cells and ploidy in the comet assay - Brunborg, Gunnar; Collins, Andrew; Graupner, Anne; Gutzkow, Kristine B.; Olsen, Ann-Karin (Frontiers in Genetics, 2015)
In the comet assay, single cells are analyzed with respect to their level of DNA damage. Discrimination of the individual cell or cell type based on DNA content, with concomitant scoring of the DNA damage, is useful since this may allow analysis of mixtures of cells. Different cells can then be characterized based on their ploidy, cell cycle stage, or genome size. We here describe two applications of such a cell type-specific comet assay: (i) Testicular cell suspensions, analyzed on the basis of their ploidy during spermatogenesis; and (ii) reference cells in the form of fish erythrocytes which can be included as internal standards to correct for inter-assay variations. With standard fluorochromes used in the comet assay, the total staining signal from each cell – whether damaged or undamaged – was found to be associated with the cell’s DNA content. Analysis of the fluorescence intensity of single cells is straightforward since these data are available in scoring systems based on image analysis. The analysis of testicular cell suspensions provides information on cell type specific composition, susceptibility to genotoxicants, and DNA repair. Internal reference cells, either untreated or carrying defined numbers of lesions induced by ionizing radiation, are useful for investigation of experimental factors that can cause variation in comet assay results, and for routine inclusion in experiments to facilitate standardization of methods and comparison of comet assay data obtained in different experiments or in different laboratories. They can also be used - in combination with a reference curve - to quantify the DNA lesions induced by a certain treatment. Fish cells of a range of genome sizes, both greater and smaller than human, are suitable for this purpose and they are inexpensive.